(untitled) (International Journal of Physiotherapy, 2015)
Background: Pressure ulcers are injuries to skin and underlying tissues resulting from prolonged pressure on the skin which often develop on skin that covers bony areas of the body, such as the heels, ankles, hips and sacrum. Without care, pressure ulcers continue to grow in diameter and depth and are exceptionally difficult to heal. Therefore, enormous effort is required to find effective and reliable techniques for preventing the initiation of ulcers and eliminating them once they develop. This study has been done to assess the efficacy of low intensity laser therapy (LILT) on the wound healing dynamics in human subjects with pressure ulcers using Bates Jensen wound assessment tool. Methods: A total of 130 subjects were enrolled for the study and after randomization the subjects were allocated to control and experimental groups each consisting of 65 subjects. The subjects of the control group received conventional wound dressing for the pressure ulcer for 3 weeks where as the subjects of the experimental group underwent LILT and conventional wound dressing for 3 weeks. On Day 1 and after 3 weeks, the BWAT score of the pressure ulcer was recorded. Results: The results showed a significant difference between pre and post intervention values in experimental group compared to control group (p< 0.05). Conclusion: The study has brought out that LILT has better healing of pressure ulcers when compared to the conventional wound management to compare the wound healing dynamics among the subjects in the control and experimental groups.